Orthodox Christians and Muslims in Cappadocia : Local Interactions in an Ottoman Countryside (1839-1923) - Tapia, Aude Aylin de, (Christians and Jews in Muslim Societies ;, 2023)
This book traces the history of everyday relations of Greek-Orthodox Christians and Muslims of Cappadocia, an Ottoman countryside inhabited by various ethno-religious groups, either sharing the same settlements, or living in neighbouring villages. Based on Ottoman state archives, testimonies collected by the Centre of Asia Minor Studies, and various pre-1923 hand-written and printed sources mostly in Ottoman- and Karamanli-Turkish, and Greek, the study covers the period from 1839 to 1923 and proposes an anthropological perspective on everyday cross-religious interactions. It focuses on questions such as identification and mapping of communities, sharing of space and resources, use of languages, and religiosity in the context of conversions and of shared sacred spaces and beliefs to investigate everyday realities of a multireligious rural society which disappeared with the fall of the Empire.